How country size matters for institutional change: comparing skill formation policies in Germany and Switzerland. Issue 4 (2nd October 2021) - Graf, Lukas
ABSTRACT: This paper argues that country size can play a crucial role in shaping the type of gradual change observed in collective skill formation systems. Collectively governed dual-apprenticeship training has its base in the industrial and crafts sectors of the economy and builds on the decentralised cooperation of multiple public and private stakeholders. As a result, it tends to be strongly path dependent, which favours gradual over radical forms of change. However, in recent years, dual-apprenticeship training has been increasingly challenged by the rise of the knowledge and service economy and the growing popularity of academic forms of education. In this context, I compare policy responses in Switzerland and Germany, which represent one small and one large collective skill formation system, respectively. The historical-institutionalist analysis finds that the dominant trajectory of change is conversion in Switzerland but layering in Germany, with different implications for the future viability of collective skill formation.